PENANAMAN NILAI-NILAI KARAKTER SOSIAL SISWA DALAM PENDIDIKAN KEWARGANEGARAAN DAN IPS DALAM KONTEKS PERPSPEKTIF GLOBAL - Dr Tetep (JURNAL PETIK, 2016)
The 21st century is a major challenge for thedevelopment of general education in preparing youngpeople in the nation and the wider life without limits.Education became the center of the adjustment ofeach individual role as the public face of the worldtoday. Global perspective becomes an importanteducation is taught by any educational institution inorder to give birth to a generation that is able tocompete in the global life without losing its localcharacteristics. Social character student that growsnaturally in the local life will become a symbol ofstrength and intelligence implementation of localvalues developed in the global life through educationsystem. Civic and social studies education as subjectwhich cannot be relased to the developing andchanges of society. Civic and social studieseducatioan has a major role in bridging of socialcharacter education for the student to be humanize.